Avaliação das salas de vacinação de unidades de Atenção Primária à Saúde - Maria de Fátima Pereira de Sousa Galvão; Paulo César de Almeida; Maria do Socorro Vieira Lopes; Janaína Fonseca Victor Coutinho; Mariana Cavalcante Martins; Lorena Pinheiro Barbosa (Universidade Federal do Ceará, 2019)
Objective to evaluate the vaccination rooms of primary health care units.Methods evaluative research, in which the Structure and Process in 89 vaccination rooms of six Regional Health Coordination Centers were evaluated through supervision of vaccine rooms of the Ministry of Health of Brazil.Results most of the professionals were nursing technicians (76.4%) without training in vaccination (31.5%). In the Evaluation of General Aspects/Technical Procedures, decoration objects (43.8%), absence of bench (22.5%), and insufficient number of vaccines (41.6%) were observed. In the evaluation of the Cold Chain, inadequate cleaning of refrigerators (71.9%) and inappropriate temperatures (48.8%) were found.Conclusion the evaluation of vaccine rooms showed that the structure of the General Aspects/Technical Procedures and Cold Chain components presented good classification, while the evaluation of the process of these components indicated a regular classification.